Quality of life problems in gynecological cancer patients - Rybin, A. I.; Rybina, I. P. (Journal of Education, Health and Sport, 2020)
Due to improvements in short- and long-term clinical outcomes a study of quality of life is one of the most promising trends in oncology today. This review analyzes the published literature on problems dealing with quality of life of patients with gynecological cancer. Data on quality of life with respect to the extent of anticancer treatment as well as psychological and social aspects are presented. The relationship between quality of life and survival has been estimated.